A Primer on Microeconomics - Beveridge, Thomas (Business Expert Press, 2013)
Ebook from IG Library ; Economics, far from being the 'dismal science,' offers us valuable lessons that can be applied to our everyday experiences. At its heart, economics is the science of choice and a study of economic principles allows us to achieve a more informed understanding of how we make our choices; regardless of whether these choices occur in our everyday life or in our work environment. The present text represents a common sense approach to basic microeconomics. It is directed toward all students, but particularly those within business school settings including students beginning an advanced business degree course of study. It will deliver clear statements of essential economic principles, supported by easy to understand examples, and uncluttered by extraneous material; the goal being to provide a concise readable primer that covers the substance of microeconomic theory. The text will look at the efficient operation of competitive markets and what may cause those markets to fail; the benefits from trade; profit maximization; the consequences of choice; and the implications of imperfect competition.